2013
DOI: 10.1098/rspb.2012.2543
|View full text |Cite
|
Sign up to set email alerts
|

A family of diatom-like silicon transporters in the siliceous loricate choanoflagellates

Abstract: Biosilicification is widespread across the eukaryotes and requires concentration of silicon in intracellular vesicles. Knowledge of the molecular mechanisms underlying this process remains limited, with unrelated silicontransporting proteins found in the eukaryotic clades previously studied. Here, we report the identification of silicon transporter (SIT)-type genes from the siliceous loricate choanoflagellates Stephanoeca diplocostata and Diaphanoeca grandis. Until now, the SIT gene family has been identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 72 publications
1
56
0
Order By: Relevance
“…This is exemplified by the distribution of Si transporters in the metazoans and their sister group, the choanoflagellates (Marron et al, 2013). SIT-Ls were identified from all three of the main bilaterian groups: lophotrochozoans (polychaete annelid worms), ecdysozoans (copepods) and deuterostomes (tunicates).…”
Section: Changing Si Biogeochemistry In the Precambrian Oceansmentioning
confidence: 99%
“…This is exemplified by the distribution of Si transporters in the metazoans and their sister group, the choanoflagellates (Marron et al, 2013). SIT-Ls were identified from all three of the main bilaterian groups: lophotrochozoans (polychaete annelid worms), ecdysozoans (copepods) and deuterostomes (tunicates).…”
Section: Changing Si Biogeochemistry In the Precambrian Oceansmentioning
confidence: 99%
“…Diatoms are known to have rigid cell walls (frustules) composed of amorphous silica (SiO2) which is released upon cell lysis. 24,25 The SSA spectrum categorized as polysaccharides (Figure 1f) features skeletal C-C, C-O and stretching C-C-O bands at 991 and 1044 cm -1 , CH2 bending vibration that typically appears at 1459 cm -1 in lipids, a peak at 1642 cm -1 that can be either C=O stretching in carbohydrates or C=C stretching vibration of unsaturated fatty acid chains and a broad peak at 2929 cm -1 identified as the C-H stretching modes of -CH-, methylene (-CH2-) and terminal methyl (-CH3) groups of fatty acid chains. 26,27 This spectrum obtained from SSA was compared with the spectrum of commercially available standards representative of cellular polysaccharides: lipopolysaccharide (LPS) from E. coli, lamanarin, inulin, sodium alginate and peptidoglycan.…”
Section: Types Of Organic Compounds Identified In Ssa By Ramanmentioning
confidence: 99%
“…[4][5][6]9,14,22 The OM fraction of SSA depends on size and varies in composition; field studies have reported that the majority of OM in the bulk submicrometer marine aerosol is relatively water insoluble and that in supermicrometer SSA is mostly water soluble. [12][13][14][23][24][25][26] Spectroscopic measurements of SSA particles collected in the field have shown that the oxygen-rich organic fraction of individual particles contains molecules with spectral signatures that are characteristic of saccharides, 24 and signatures for carboxylic acids 26 and alkanes 27 have also been observed.…”
Section: The Bigger Picturementioning
confidence: 99%
“…Silicification in sponges involves a different set of organic constituents (references in Wallace et al 2012), demonstrating that distinct proteins and polysaccharides have been recruited for silica skeletogenesis in different silicifying clades. In this regard, it is curious that preliminary molecular research on silica precipitation in choanoflagellate loricae (e.g., Gong et al 2010) indicates that silicon transporters in this group are related to those in diatoms, implying lateral genetic transfer (Marron et al 2013). Not much is known about the molecular biology of silification in radiolaria or other groups.…”
Section: Silica Use By Protistsmentioning
confidence: 99%